A histochemical study of tissue eosinophilia in oral squamous cell carcinoma using Congo red staining - Priya Shirish Joshi; Manasi S Kaijkar (Wolters Kluwer Medknow Publications, 2013)
Background: Tumor associated tissue eosinophilia is believed to play a significant role in the biological behavior of the carcinoma. Eosinophil infiltrate in association with the head and neck squamous cell carcinoma (SCC) have been reviewed from time-to-time. The significance of such an association has been variably thought to be either a potential diagnostic tool for stromal invasion or as a prognostic indicator. We aimed to evaluate the efficacy of Congo red staining to differentiate eosinophils in the inflammatory infiltrate in oral squamous cell carcinoma (OSCC) and whether this eosinophilia is associated with the histologic grading in OSCC. Materials and Methods: The eosinophil infiltration in hematoxylin and eosin (H and E) and Congo red stained sections of 50 biopsies of OSCC were examined. The eosinophil distribution was quantitatively evaluated in both sections as either diffuse or focal and scored as mild, moderate and severe grades. The average number of eosinophils obtained in OSCC stained by H and E and Congo red were then statistically compared by univariate analysis carried out using Student's t-test. P < 0.01 was used to determine the statistical significance. Results: In the OSCC, the eosinophil infiltration was seen in 43 out of 50 (86%) cases. The elevation of eosinophil count was more diffuse than focal (36 vs. 7 [83.72 vs. 16.27%]). The staining efficacy of Congo red stain over H and E stain to differentiate eosinophils was excellent and found to be statistically significant (P < 0.01). No significant correlation was found with the eosinophil infiltration and the histologic grades of OSCC. Conclusion: Our study showed a strong infiltration of eosinophils in OSCC though no significant correlation was found with the eosinophil infiltration and the histologic grades of OSCC. Congo red staining showed a high sensitivity in staining eosinophils over routine H and E. This staining technique could therefore provide an adjunct to routine H and E in evaluating eosinophils in dysplasia and OSCC cases.